Authority of the consumer dispute resolution board (bpsk) in resolving consumer disputes in the financial services sector - Pujiono, Bambang (Journal of Law Science, 2024)
This research presents the fact that there is a legal urgency that must be immediately regulated in regulations related to the object of research, namely the resolution of financial services disputes through the Consumer Dispute Resolution Agency (BPSK). The research was carried out using the literature study method, namely a normative approach, namely conducting a study of primary legal materials in the form of statutory regulations -invitations, books or other literature relevant to the legal issues being discussed. The research results show that there is a conflict of norms and a conflict of authority regarding dispute resolution in the financial services sector, this can result in less than optimal implementation of consumer protection as mandated by Law N0 8 of 1999 concerning Consumer Protection